2004
DOI: 10.1002/jcb.20118
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress triggers an acute proteasome‐dependent degradation of ATF6

Abstract: ATF6, a 670 amino acid endoplasmic reticulum (ER) transmembrane glycoprotein with the electrophoretic mobility of a 90 kDa protein, is a key transcriptional activator of the unfolded protein response (UPR) that allows mammalian cells to maintain cellular homeostasis when the cells are subjected to a variety of environmental and physiological stress. Previous studies have established that ATF6 is a short-lived protein, the activation of which involves relocation from the ER to the Golgi where it is cleaved by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 40 publications
4
64
2
4
Order By: Relevance
“…It was suggested that GRP78 binds to PERK (and also IRE1 and ATF6) and inactivates PERK's ER stress response inducing capabilities under nonstress conditions; when ER stressors accumulate unfolded proteins in the ER, PERK (and also IRE1 and ATF6) is activated to induce the ER stress response by releasing GRP78 from PERK, as a result of the binding of unfolded proteins to GRP78 (Bertolotti et al, 2000;Shen et al, 2002a). Induction of GRP78 by proteasome inhibitors has been reported (Hong et al, 2004). It was reported that overexpression of GRP78 inhibited the phosphorylation of PERK in the presence of an ER stressor (thapsigargin) (Bertolotti et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that GRP78 binds to PERK (and also IRE1 and ATF6) and inactivates PERK's ER stress response inducing capabilities under nonstress conditions; when ER stressors accumulate unfolded proteins in the ER, PERK (and also IRE1 and ATF6) is activated to induce the ER stress response by releasing GRP78 from PERK, as a result of the binding of unfolded proteins to GRP78 (Bertolotti et al, 2000;Shen et al, 2002a). Induction of GRP78 by proteasome inhibitors has been reported (Hong et al, 2004). It was reported that overexpression of GRP78 inhibited the phosphorylation of PERK in the presence of an ER stressor (thapsigargin) (Bertolotti et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress triggered by Ca 2ϩ depletion induces the formation of a nascent, partially glycosylated form of ATF6␣ with reduced interaction with calreticulin and faster rate of traverse to the Golgi, resulting in higher transactivation of N-ATF6␣ gene targets. 42 Because an accumulation of underglycosylated proteins in the ER has the ability to induce the UPR, the glycosylation status of ATF6␣ may serve as a novel sensor of glycoprotein homeostasis, leading to activation of the UPR. There are 2 isoforms of ATF6 (ATF6␣ and ATF6␤) that are characterized by their divergent transcriptional activity domains.…”
Section: Atf6 Pathwaymentioning
confidence: 99%
“…Additionally, we analyzed endogenous atf6 mRNA levels in WNV-infected SK-N-MC cells and did not observe any changes, indicating that the difference occurs at a posttranscriptional step (data not shown). Previous studies have shown rapid degradation of ATF6 upon ER stress, in a proteasomedependent manner (16). To confirm if ATF6 degradation in WNV infection occurs in a similar fashion, WNV-infected cells were treated at 36 h p.i.…”
Section: Wnv Infection Leads To Induction Of Er Chaperonesmentioning
confidence: 99%